Wnt/β‐catenin signaling during early vertebrate neural development. Issue 11 (21st August 2017) - Brafman, David; Willert, Karl
ABSTRACT: The vertebrate central nervous system (CNS) is comprised of vast number of distinct cell types arranged in a highly organized manner. This high degree of complexity is achieved by cellular communication, including direct cell‐cell contact, cell‐matrix interactions, and cell‐growth factor signaling. Among the several developmental signals controlling the development of the CNS, Wnt proteins have emerged as particularly critical and, hence, have captivated the attention of many researchers. With Wnts' evolutionarily conserved function as primordial symmetry breaking signals, these proteins and their downstream effects are responsible for simultaneously establishing cellular diversity and tissue organization. With their expansive repertoire of secreted agonists and antagonists, cell surface receptors, signaling cascades and downstream biological effects, Wnts are ideally suited to control the complex processes underlying vertebrate neural development. In this review, we will describe the mechanisms by which Wnts exert their potent effects on cells and tissues and highlight the many roles of Wnt signaling during neural development, starting from the initial induction of the neural plate, the subsequent patterning along the embryonic axes, to the intricately organized structure of the CNS. © 2017 Wiley Periodicals, Inc. Develop Neurobiol 77: 1239–1259, 2017